The role of the Pin1-cis P-tau axis in the development and treatment of vascular contribution to cognitive impairment and dementia and preeclampsia - Qiu, Chenxi; Li, Zhixiong; Leigh, David A.; Duan, Bingbing; Stucky, Joseph E.; Kim, Nami; Xie, George; Lu, Kun Ping; Zhou, Xiao Zhen (Frontiers in Cell and Developmental Biology, 2024)
Tauopathies are neurodegenerative diseases characterized by deposits of abnormal Tau protein in the brain. Conventional tauopathies are often defined by a limited number of Tau epitopes, notably neurofibrillary tangles, but emerging evidence suggests structural heterogeneity among tauopathies. The prolyl isomerase Pin1 isomerizes cis P-tau to inhibit the development of oligomers, tangles and neurodegeneration in multiple neurodegenerative diseases such as Alzheimer’s disease, traumatic brain injury, vascular contribution to cognitive impairment and dementia (VCID) and preeclampsia (PE). Thus, cis P-tau has emerged as an early etiological driver, blood marker and therapeutic target for multiple neurodegenerative diseases, with clinical trials ongoing. The discovery of cis P-tau and other tau pathologies in VCID and PE calls attention for simplistic classification of tauopathy in neurodegenerative diseases. These recent advances have revealed the exciting novel role of the Pin1-cis P-tau axis in the development and treatment of vascular contribution to cognitive impairment and dementia and preeclampsia.